A prospective, multicenter study to evaluate the effectiveness and safety of prochlorperazine in patients suffering from vestibular migraine - Ilambarathi, M.; Yeolekar, Aditya; Roy, Dhrubo; Saxena, Savyasachi; Kumar, Suresh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Background: Prochlorperazine is commonly used for managing vertigo and dizziness-associated vestibular disorders. This study was designed to evaluate the effectiveness and safety of prochlorperazine in Indian patients with vestibular migraine. Methods: In this prospective, multicenter, open-label, single-arm study, VM patients received 5 mg of prochlorperazine thrice daily for 5 days. The primary endpoint measured changes in clinical response using the scale for vestibular vertigo severity level and clinical response evaluation from baseline to days 6, 15, and 30. Secondary endpoints included symptom severity improvement and changes in SVVSLCRE from baseline up to day 30. Safety and tolerability were also assessed. Statistical analysis used the Wilcoxon signed-rank test and student-paired t-test. Results: Out of 259 enrolled patients, 254 (98.1%) completed the study with a mean (standard deviation) age of patients was 42.22 (10.7) years; 72.2% were females. Significant improvements in clinical response and symptom severity were observed at all follow-up periods. 81.5% of patients showed VM symptom improvement by day 6, with 77.2% exhibiting moderate to good changes in SVVSLCRE scores. 83.4% experienced milder vestibular symptoms after 6 days. Furthermore, a significant difference (p<0.001) in mean values was observed from baseline at different follow-up periods. 11 (4.3%) adverse events (AEs) were reported, with headache being the most common (2, 0.8%); all AEs were unrelated to the study drug, and patients reported good tolerability. Conclusions: Prochlorperazine showed significant improvement in clinical response and symptom severity with acceptable safety and tolerability in VM patients.